DYNAMICS OF CONCENTRATION OF APOPTOSIS SERUM MARKERS IN ASSESSMENT OF PROGNOSIS OF CHRONIC KIDNEY DISEASE IN CHILDREN - O. V. Komarova; A. G. Kucherenko; I. E. Smirnov; A. N. Tsygin (Вопросы современной педиатрии)
Aim: to investigate sFas-receptor and its ligand, sFas-L, cytochrome C and annexin V as the apoptotic markers in children with CKD to determine the renal cell apoptosis role in the progression of a renal disease. Patients and methods: 68 children with CKD 1–3 from 3 to 17 years were examined. Results: sFas-R, sFas-L, annexin V significant differed from normal value at all stages of CKD. Cytochrome C level was significantly higher than normal in children with CKD1. But tended to increase at and 2 and 3 stages correspondingly. Significant correlation was determinated between proteinuria and the combination of all four markers. Сomparing serum levels of apoptosis markers in children with non-immune disorders without renal dysfunction treated and iACE not treated and in patients with CKD-2 t a significant excess of the level of sFas-R in patients without iACE therapy was found. Conclusions: Fas-mediated and mitochondrial programmed cell death are implicated in development and progression of CKD. ACE inhibitors reduced the severity of apoptosis, primarily by inhibiting the activity of its Fas-mediated pathway.